2003
DOI: 10.1046/j.1469-8137.2003.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and growth responses of the montane bryophyte Racomitrium lanuginosum to atmospheric nitrogen deposition

Abstract: Summary• The effects of nitrogen (N) deposition on the moss Racomitrium lanuginosum within montane heath in Scotland were investigated over 5 yr.• Permanent field plots were sprayed with KNO 3 or NH 4 Cl solutions, at doses equivalent to 10 and 40 kg N ha − 1 yr − 1 , in 3 -6 applications each summer.• Racomitrium growth and cover were severely reduced by N addition, whilst the proportion of dead shoots greatly increased. N dose decreased inducibility of shoot nitrate reductase activity (NRA), suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
93
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 36 publications
11
93
1
3
Order By: Relevance
“…In studies comparing the effects of NO 3 -and NH 4 + (at the same N concentration) on vascular plants, NH 4 + stress typically led to reduction in growth and survival rate, increased tissue N (often also P) concentration, and decreased tissue cation concentrations (Gigon & Rorison, 1972;De Graaf et al, 1998;Lucassen et al, 2003). Comparatively few studies have studied the separate effects of NO 3 -and NH 4 + on bryophytes and these have revealed the same patterns as described above for vascular plants (Soares & Pearson, 1997;Pearce et al, 2003). It has also been shown that NH 4 + toxicity can cause a decline in bryophyte cover (Krupa, 2003;Pearce et al, 2003).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In studies comparing the effects of NO 3 -and NH 4 + (at the same N concentration) on vascular plants, NH 4 + stress typically led to reduction in growth and survival rate, increased tissue N (often also P) concentration, and decreased tissue cation concentrations (Gigon & Rorison, 1972;De Graaf et al, 1998;Lucassen et al, 2003). Comparatively few studies have studied the separate effects of NO 3 -and NH 4 + on bryophytes and these have revealed the same patterns as described above for vascular plants (Soares & Pearson, 1997;Pearce et al, 2003). It has also been shown that NH 4 + toxicity can cause a decline in bryophyte cover (Krupa, 2003;Pearce et al, 2003).…”
Section: Discussionmentioning
confidence: 64%
“…It is well established that, because of their anatomy, bryophytes take up deposited elements very efficiently. However, this trait also makes them vulnerable, to a higher degree than vascular plants, to increased N deposition (Mäkipää, 1998;Proctor, 2000;Pearce et al ., 2003). Importantly, there are indications that at high deposition rates, NH 4 + may be more detrimental than NO 3 -, as Pearce et al .…”
Section: Introductionmentioning
confidence: 99%
“…Membrane damage to 'black' (lower) tissue has been reported in another montane moss Racomitrium lanuginosum (Hedw.) Brid (Pearce et al, 2003). Cell membranes play important roles in nutrient uptake and conservation (Glime, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Moss samples were oven dried, and the top 2 cm of shoots selected for analysis [11] to reflect recent growth. Samples were ground by ball mill and analysed for N and C concentration on a Fisons NA1500 NCS elemental analyser.…”
Section: Methodsmentioning
confidence: 99%
“…Thus whilst vascular plant N concentration is linked to soil N availability, moss N concentration is associated with atmospheric N deposition [10,11]. N deposition levels are lower in the Arctic than in heavily industrialised areas including northern Europe [12]; thus, a decrease in N concentration of moss in relation to latitude may be expected.…”
Section: Introductionmentioning
confidence: 99%